An effective optoelectronic mixing method based on bulk KTN crystal. (January 2022) - Lv, Xiaolei; Zhao, Jiguang; Du, Xiaoping; Zhao, Beilei; Song, Huahua; Song, Yishuo; Chen, Hang
Highlights: The proposed optoelectronic mixing method performs well when facing the application situation requiring a large field of view. Comparing with four existing mixing methods, the proposed optoelectronic mixing method achieves a well mixing efficiency even if the power consumption is increased. Abstract: An effective optoelectronic mixing (OEM) method based on bulk potassium tantalate niobate (KTN) crystal was proposed. The optical isotropy of the cubic phase rendered KTN insensitive to the incident angles of collected beams. Consequently, effective electro-optic (EO) modulation could be realized under a large incident range of 20°. The massive quadratic EO coefficient of 3.7 × 10 −15 m 2 /V 2 could effectively reduce local oscillation (LO) voltage, such that OEM could be achieved under low power consumption. On the basis of the above advantages, a mixing efficiency model for KTN mixer was proposed to describe mixing characteristics. Simultaneously, a mixing efficiency of 44% within the 20° incident range was achieved at a power consumed for each pixel of 230 μW.